2011
DOI: 10.1002/chem.201101066
|View full text |Cite
|
Sign up to set email alerts
|

Guest‐Release Control in Enzyme‐Sensitive, Amphiphilic‐Dendrimer‐Based Nanoparticles through Photochemical Crosslinking

Abstract: Stimuli sensitive, facially amphiphilic dendrimers have been synthesized and their enzyme-responsive nature has been determined with dual fluorescence responses of both covalently conjugated and non-covalently bound reporter units. These dual responses are correlated to ascertain the effect of enzymatic action on micellar aggregates and the consequential guest release. The release of the guest molecule is conveniently tuned by stabilizing the micellar aggregates through photochemical crosslinking of hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 79 publications
3
61
0
Order By: Relevance
“…Our group introduced coumarin into dendrimers as a reversible cross-linker to control the accessibility of substrate in the dendrimer assembly (see Figure 28) [66]. When the assembly solution was exposed to UV light (365 nm), the enzymatic degradation of substrate was highly suppressed since the ester groups were confined in the interior of assembly.…”
Section: Methods Of Synthesis Of Nanogelsmentioning
confidence: 99%
“…Our group introduced coumarin into dendrimers as a reversible cross-linker to control the accessibility of substrate in the dendrimer assembly (see Figure 28) [66]. When the assembly solution was exposed to UV light (365 nm), the enzymatic degradation of substrate was highly suppressed since the ester groups were confined in the interior of assembly.…”
Section: Methods Of Synthesis Of Nanogelsmentioning
confidence: 99%
“…116 In this case, we monitored enzymatic cleavage reaction using the release of a covalently conjugated fluorophore, 4-methylumbelliferone (MUF) (Fig.20). Concurrent monitoring of MUF fluorescence and that of a non-covalently encapsulated fluorophore suggested that there is a clear correlation between the kinetics of the enzymatic reaction and that of the guest molecule release.…”
Section: Stimuli Responsive Dendrimersmentioning
confidence: 99%
“…Here, we have also found that monomer-aggregate equilibrium plays an important role on the enzymatic cleavage and the ensued guest molecule release. 86 Currently studies are underway in our laboratory to discern alternate pathways, if any, involved to affect the non-covalent guest molecule release from these nanocontainers.…”
Section: Protein Sensitive Amphiphilic Dendrimersmentioning
confidence: 99%